Effectiveness of Cognitive Behavior Modification Group Counseling with Cognitive Restructuring Techniques to Prevent Exposure to Pornography - Pu'ad Maulana; Yeni Karneli; Ifdil; Miftahul Fikri (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The exposure of pornography among adolescents is increasingly worrying because it has a negative impact on psychological, social, academic, and moral aspects. This study aims to test the effectiveness of Cognitive Behavior Modification (CBM)-based group counseling services using cognitive restructuring techniques in preventing exposure to pornography among students. The method used was a quasi-experiment with a non-equivalent control group design. The research subjects were 17 students from Senior High Schools in Sarolangun , selected via cluster random sampling: 9 in the experimental group and 8 in the control group. The research instrument contained 34 valid and reliable items that measured sound, reading, images, and actions. Data analysis used the Wilcoxon Signed-Rank Test and the Mann-Whitney U Test. The results showed that the experimental group experienced a significant decrease in pornography exposure scores from high to low, with an N-Gain of 34.8. In contrast, the control group only had an N-Gain of 15.5. The Mann-Whitney U test resulted in p = 0.048 (< 0.05). These findings confirm that CBM is effective as a preventive strategy and can be implemented by guidance and counseling teachers to help students deal with the challenges of pornography exposure. Keywords: group counseling, cognitive behavior modification, cognitive restructuring, pornography exposure